Serum uric acid is a determinant of metabolic syndrome in a population-based study - Onat, Altan; Uyarel, Huseyin; Hergenc, Gulay; Karabulut, Ahmet; Albayrak, Sinan; Sari, Ibrahim; Yazici, Mehmet; Keles, Ibrahim (OXFORD UNIV PRESS, 2006)
Background: Determination of serum uric acid concentrations and role in risk of metabolic syndrome (MS) were investigated in 1877 participants in a cross-sectional population-based study including a brief follow-up. Methods: The MS was identified by modified criteria of the Adult Treatment Panel III, and coronary heart disease (CHD) by clinical findings and Minnesota coding of resting electrocardiograms. Uric acid concentrations were measured by the uricase method. Results: Metabolic syndrome was present in 39.1% of the cohort. Linear regression analysis of uric acid levels in a model comprising 13 variables identified gender, waist girth, total cholesterol (TC), alcohol usage, triglycerides, log C-reactive protein (CRP), and log gamma-glutamyl transferase (GGT), and in women diuretic use and elevated blood pressure (BP), as significant independent covariates whereby the largest contribution (1.6 mg/dL) was generated by waist girth. Logistic regression analysis of serum uric acid for MS disclosed for the top versus the bottom tertile an odds ratio (OR) of 1.89 (95% confidence interval [CI]: 1.45-2.46) in men and women combined, after ajustment for sex, age, TC, log CRP, log GGT, alcohol, and diuretic drug use, presence of diabetes/impaired fasting glucose, elevated BP, and smoking status. This corresponded to an increase by 35% in MS likelihood for each 1 SD uric acid increment. This rate declined to a significant 15% by inclusion of waist girth into the model. The OR of uric acid concentrations for prevalent and incident CHD, adjusted for age, MS, smoking, and diuretic use, was not significant among women and only tended toward significance in men. Conclusions: Abdominal obesity is the main determinant of uric acid variance. An increment of 1 SD in serum uric acid levels are associated in both sexes with a 35% higher MS likelihood, independent of 10 risk factors related to MS. After adjustment for waist girth, a more modest but significant likelihood persists, which suggests that serum uric acid is a determinant of MS.
Keywords: abdominal obesity; coronary heart disease risk; hypertension; metabolic syndrome; population-based study; serum uric acid; VISCERAL FAT ACCUMULATION; CORONARY-HEART-DISEASE; CARDIOVASCULAR-DISEASE; INSULIN-RESISTANCE; FOLLOW-UP; PLASMA-GLUCOSE; RISK-FACTORS; HYPERURICEMIA; OBESITY; COMPONENTS; Cardiovascular System & Cardiology